Trick of the Light. - Elvery, Laura (University of Queensland Press, 2018)
An art teacher sends four of her students on a guerrilla mission. A young runner struggles to make sense of his best friend's death. A health-food company adopts a farcical promotional strategy. A factory worker spends her days applying radioactive paint to watches, while dreaming of a future with her new suitor. With a keen eye for detail and rich emotional insight, Laura Elvery reveals the fears and fantasies of everyday people searching for meaning. Ranging from tender poignancy to wry humor, this beguiling collection marks the debut of one of a rising star.